The history, not so short, of neuroethics - Donato, Francesca; Donato, Annalidia; Corrado, Simona; Volpentesta, Luigina; Donato, Giuseppe (Medicina Historica, 2023)
In this paper the authors examine the discipline recently defined "Neuroethics". In the main of its meanings, it relates ethics to its neurological basis. The awareness of this relationship between the brain and moral choices emerged anciently and progressively in the history of science and philosophy. Inspite of the great development of neuroscience and the variegated articulations of moral philosophy, the term Neuroethics is still in search of its meaning.